2006
DOI: 10.1002/app.23664
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosilylation reaction of methylhydridesiloxane to phenylacetylene

Abstract: ABSTRACT:The hydrosilylation reaction of ␣,-bis(trimethylsiloxy)methylhydridesiloxane to phenylacetylene in the presence of catalyst-platinum hydrochloric acid (0.1M solution in tetrahydrofuran)-at 1 : 35 ratio of initial compounds, at various temperatures (40 -60°C) was investigated and methylsiloxane oligomers with phenethenyl substituted groups in the side chain has been obtained. It was shown that complete hydrosilylation of all active (SiOH groups do not take place. The hydrosilylation reaction order, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Other hydrosilylation reactions were carried out according to the previously discussed method. The amount selected for platinum hydrochloric acid was 5–9 × 10 −5 g/1.0 g of starting substance 3, 4…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other hydrosilylation reactions were carried out according to the previously discussed method. The amount selected for platinum hydrochloric acid was 5–9 × 10 −5 g/1.0 g of starting substance 3, 4…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we investigated hydrosilylation reactions of PMHS with styrene, α‐methylstyrene, and phenylacetylene 3, 4. In this work, we continue to present the syntheses and investigations of polysiloxanes with aromatic fragments in the side chain to determine the correlation between the chemical composition of the polymer and phase‐transition temperatures.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We tentatively assigned these peaks to trapped hexane solvent and/or aliphatic groups (methylene and methine) resulted from branching process between the surface Si-CH=CH-groups during drying the samples. 6 Without any in situ evidences, we assumed that the methoxy ions generated from the reaction between MeOH and LiAlH 4 in the quenching step, step 2 in Scheme 1, could react with H-Si QDs to form partial Si-OMe termination, which was further converted into oxidized components during the purification steps. The oxidation of H-Si QD surface by alkoxy has been reported previously in the microplasma reaction, where ethanol solvent was dissociated into ethoxy ions by reacting with plasma electron.…”
Section: Notesmentioning
confidence: 99%
“…The hydrosilylation of styrene, ␣-methylstyrene, phenylacetylene [107,108] allyl methoxybenzene and allyl dimethoxybenzene [109], in the presence of Karstedt's catalyst and H 2 PtCl 6 in THF, showed that Karstedt's catalyst is more efficient in the reactions examined.…”
Section: Mementioning
confidence: 99%